Coevolution of Weathering Front and Water Table. Issue 20 (21st October 2021) - Wang, Wei; Chen, Po; Dueker, Ken; Zhang, Ye; Lee, En‐jui; Mu, Dawei; Keifer, Ian; Jiao, Jianying
Abstract: Water is known to play an essential role in initiating and maintaining subsurface weathering reactions. However, the interaction between the weathering front and the water table is unclear and under intense debate. Here, we present a high‐fidelity, 3D image of a variably saturated weathering front beneath a granite terrain in the Laramie Range, Wyoming, constructed using full‐3D ambient‐noise adjoint tomography and calibrated with data from an extensive drilling and hydraulic well testing effort. The imaged weathering front between saprolite and weathered bedrock is overall shallower than the water table under ridge but deeper than water table under valleys. We propose that downward‐advancing weathering front coevolves with water table in a positive cycle that gradually flattens the water table, enhances the rate of groundwater drainage, and exposes underlying bedrock to weathering. As a result, we expect this cycle to become "sluggish" with time as water table gradient decreases. Plain Language Summary: Weathering between saprolite and weathered bedrock plays a significant role in ecosystem and Critical Zone processes, but the mechanisms and feedbacks that control the depth and structure of the weathering front are largely unknown. Several weathering models suggest that the weathering front is set by and colocated with the water table, which is however not observed at our study site underneath a granite terrain in the Laramie Range of Wyoming. By combining the latest seismic tomography technique with direct water‐level measurements from boreholes, we were able to construct a 3D, high‐fidelity image of the weathering front under the granite terrain along with a map of mean water table position. We found that the weathering front has a slightly larger peak‐to‐trough relief than the water table. Considering evidences of estimated subsurface porosity and hydraulic conductivity at the site, we propose that the shape of the water table is being actively modified by weathering driven by infiltration of meteoric water from the land surface. Specifically, due to the downward advancement of the weathering front and the accompanying increases in subsurface porosity and hydraulic conductivity, the rate of groundwater drainage increases and as a result, the water table is losing curvature. Key Points: We construct three‐dimensional shear‐wave velocity and porosity models of the Critical Zone under a granite terrain, Wyoming Saprolite bottom is shallower than the water table under ridge but deeper than the water table under valleys Coevolution of weathering front and water table can explain the existence of thick saprolite beneath the water table under ridge